The effect of tislelizumab on complete and pathological complete response in non-small cell lung cancer: a systematic review and meta-analysis - Feng, Qian; Yan, Xiaoxia; Gao, Liping; Li, Hui; Sarah, Baik; Anna, Russo; Jiang, Hongying (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors have transformed non-small cell lung cancer (NSCLC) treatment, and while overall survival (OS) and progression-free survival (PFS) are well-established, a comprehensive meta-analysis focusing on complete response (CR) and pathological complete response (pCR) with tislelizumab-based therapies in NSCLC is lacking.MethodsThis systematic review and meta-analysis was conducted following PRISMA guidelines. A thorough literature search was performed across PubMed, Embase, and Web of Science. We included both randomized controlled trials and observational studies of tislelizumab in NSCLC, focusing on extracting data for radiological complete response (CR, based on RECIST 1.1 criteria) and pathological complete response (pCR, defined as absence of residual invasive cancer in resected surgical specimens). Risk of bias was assessed using the Cochrane Collaboration’s tool and the Newcastle-Ottawa Scale. Statistical analyses were performed using the ‘meta’ package in R. 95% confidence intervals (CIs) and odds ratios (ORs) were calculated for CR and pCR, and subgroup analyses were conducted.Results7 studies were enrolled in the meta-analysis. The results on pCR showed significant heterogeneity (I2 = 92.5%), with a random effects OR of 2.1103 (95% CI: 0.5195 to 8.5727). Subgroup analysis for pCR by disease type revealed a statistically significant difference between NSCLC and SCC only subgroups under the common effect model (p < 0.001). Furthermore, the pCR subgroup analysis by comparator drug showed a statistically significant difference (p < 0.0001) between Pembrolizumab+Chemotherapy (OR 0.6968, 95% CI: 0.3803 to 1.2767) and Chemotherapy alone (OR 7.3123, 95% CI: 2.9204 to 18.3092). For CR, the meta-analysis demonstrated minimal heterogeneity (I2 = 0.0%), yielding a significant random effects OR of 2.6277 (95% CI: 1.2858 to 5.3699). Subgroup analysis for CR comparing tislelizumab plus chemotherapy to chemotherapy alone showed a significant advantage (OR 3.8690, 95% CI: 1.5423 to 9.7059).ConclusionTislelizumab combined with chemotherapy significantly improves CR rates in NSCLC compared to chemotherapy alone. While pCR data exhibit high heterogeneity, the findings highlight tislelizumab’s role in achieving deep tumor responses.